1993
DOI: 10.1021/ac00065a018
|View full text |Cite
|
Sign up to set email alerts
|

Core and valence band photoelectron spectroscopic studies of nickel oxidation in an anaerobic liquid cell

Abstract: An apparatus is described that allows studies to be made of the solid-liquid interface. The apparatus is linked to an X-ray photoelectron spectrometer, allowing an investigation of the changes in surface chemistry at this interface. The corrosion of nickel under various conditions is examined using this apparatus. This study focuses on the surface chemical changes associated with the exposure of nickel to deoxygenated and oxygenated solutions of water and sodium chloride. Deoxygenated water causes negligible o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…To do this, XPS measurements have also been performed on the Ni-covered samples with F treatment and 400 o C annealing. The direct determination of VBM-E F of Ni/AlGaN is difficult as the VB spectra of Ni metal dominate the high kinetic energy region of the spectrum [17], as shown in Fig. 4.…”
Section: Modification Of the Intrinsic Sbh φβ By Cf 4 Plasma Treatmentmentioning
confidence: 99%
“…To do this, XPS measurements have also been performed on the Ni-covered samples with F treatment and 400 o C annealing. The direct determination of VBM-E F of Ni/AlGaN is difficult as the VB spectra of Ni metal dominate the high kinetic energy region of the spectrum [17], as shown in Fig. 4.…”
Section: Modification Of the Intrinsic Sbh φβ By Cf 4 Plasma Treatmentmentioning
confidence: 99%
“…This ''anaerobic cell'' is specially designed to allow study of the solid-liquid interface by liquid exposure or electrochemical treatment under inert atmosphere. 3 The base pressure of the system is better than 10 Ϫ9 Torr.…”
Section: Methodsmentioning
confidence: 99%
“…3 We have found that a number of metals ͑aluminum, 1 iron, 1 and copper 2 ͒ when exposed to deoxygenated orthophosphoric acid at negative potentials ͑versus saturated calomel electrode͒, or in appropriate cases to the same acid at the rest potential, form a surface that is covered with a thin ͑less than 50 Å͒ layer of phosphate. When first exposed the phosphate is in the form of a condensed phosphate, which we believe to be in the form of metaphosphate (P 4 O 12 4Ϫ ).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 These films are interesting because they contain no oxide and are thin, generally thinner than 100 Å. 1,2 These films are interesting because they contain no oxide and are thin, generally thinner than 100 Å.…”
Section: Introductionmentioning
confidence: 99%
“…The focus of the experimental work will be the use of valence band photoemission, which we have already shown to be effective in distinguishing between phosphate and oxide, [1][2][3][4][5] and in the identification of subtle chemical differences. We report the results of two photon sources; x-ray light provides information at a greater depth than UV light allowing us to nondestructively ''profile'' through the interface region.…”
Section: Introductionmentioning
confidence: 99%